2020
DOI: 10.3390/ijms21155278
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Complexities of Glioblastoma Stem Cells: Insights for Cancer Initiation and Therapeutic Targeting

Abstract: The discovery of glioblastoma stem cells (GSCs) in the 2000s revolutionized the cancer research field, raising new questions regarding the putative cell(s) of origin of this tumor type, and partly explaining the highly heterogeneous nature of glioblastoma (GBM). Increasing evidence has suggested that GSCs play critical roles in tumor initiation, progression, and resistance to conventional therapies. The remarkable oncogenic features of GSCs have generated significant interest in better defining and characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 240 publications
(317 reference statements)
0
23
0
Order By: Relevance
“…While GBM cell lines provide vital information with regard to drug responses, it is GSCs that are thought to be the source of therapeutic resistance and tumour recurrence after surgery, and they are considered a critical target in a successful therapy approach [ 30 ]. When we analysed GSCs derived from mice overexpressing PDGFA but lacking TP53 and NF1, we found that independent of radiation the basal neurosphere formation capacity was not sensitive to sunitinib ( Figure 6 B,C).…”
Section: Resultsmentioning
confidence: 99%
“…While GBM cell lines provide vital information with regard to drug responses, it is GSCs that are thought to be the source of therapeutic resistance and tumour recurrence after surgery, and they are considered a critical target in a successful therapy approach [ 30 ]. When we analysed GSCs derived from mice overexpressing PDGFA but lacking TP53 and NF1, we found that independent of radiation the basal neurosphere formation capacity was not sensitive to sunitinib ( Figure 6 B,C).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the heterogeneity of the tumor represents one of the main characteristics in tumorigenesis, being able to determine tumor progression and treatment resistance such as resistance to chemotherapy and radiotherapy. Indeed, tumor clones resistant to the treatments are one of the predominant causes of therapy failure and tumor recurrence [ 21 ].…”
Section: Heterogeneity Of Human Glioblastomas and Glioblastoma Stem Cellsmentioning
confidence: 99%
“…Recurrent or progressive GBM usually does not respond to standard therapy, which is associated with a poor prognosis [14,15]. GSCs are a subset of cells that tolerate chemotherapy and radiotherapy and play a role in tumor recurrence [16][17][18]. Targeting GSCs and identifying new markers are the key issues involved in the development of innovative strategies to eradicate GBM [19,20].…”
Section: Introductionmentioning
confidence: 99%